Incentives for tree growing in relation to deforestation and the fuelwood crisis in Central America - Ugalde A, L.A.; Gregersen, H.M. (CATIE, Turrialba (Costa Rica). Dept. de Recursos Naturales Renovables, 2014)
22 pág, ilus, tab, 34 ref.